Development of common wheat lines with the 1BL/1RS translocation linked with the allele Glu-B1al - Kozub, N.; Sozinov, I.; Bidnyk, G.; Demianova, N.; Sozinova, O.; Karelov, A.; Blume, Ya.; Sozinov, A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2017)
A number of F6 winter common wheat lines that carry the wheat-rye 1BL/1RS translocation of the Kavkaz type with respective resistance genes linked with high bread-making quality allele Glu-B1al have been developed via marker selection among F2 plants from the cross B16 × Odesskaya krasnokolosya. The SDS-sedimentation value in these lines proved to be in most cases similar to that of the cultivar Bezostaya 1. The lines may be used as a source of the 1BL/1RS translocation linked with the high-quality allele Glu-B1al, which compensates for the negative effect of this translocation on bread-making quality.